Casos de manejo sostenible de concesiones forestales maderables en la Región Madre de Dios, Perú - Sabogal, César (2025)
In Peru, informal use of the Amazon forests predominates, in violation of the regulatory measures that regulate forest harvesting activities. Despite a series of factors that limit or hinder the application of sustainable forest management (SFM), there are positive experiences that show high standards in the management practiced over the years. The objective of this article is to show the level reached by some successful forest management initiatives in the Madre de Dios Region and how they contribute to improving the model of forest concessions for timber purposes (CFM) in the country. This model, introduced into Peruvian legislation in the 2000s, currently has more than 9.7 million hectares under concession, although the CFM that are operational cover only 2.4 million hectares. Madre de Dios is the region with the largest area of certified forest in the country, with six CFM totaling 601,535 ha. Based on a study funded by the USAID Pro-Bosques Project, two initiatives managed by concessionaire companies in this region were selected for systematization: Consolidado Maderacre S.A.C. and Consolidado Forestal Otorongo S.A.C., and one by a native community (CN): CN Bélgica. The methodology included field visits in which a guide was applied to describe the various aspects of interest for systematization, as well as interviews with various stakeholders. The results are described for each of the three initiatives, covering general information on the case, planning and implementation of forest management, environmental aspects, monitoring and research, economic and sociocultural aspects, and lessons learned. Based on the experiences of the three cases with high standards in their forest management practices, the authors highlight how they contribute to keeping the forest standing with its productive and ecosystem functions, and the challenges they face or perceive, to finally offer some guidelines that can help improve the viability of the current CFM model and take advantage of the opportunities to introduce reforms that help its scaling.